2021
DOI: 10.1002/rcs.2258
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted versus open radical cystectomy: A cohort study on perioperative outcomes accounting for stage selection bias and surgical experience

Abstract: Background Most comparisons of robot‐assisted (RARC) versus open radical cystectomy (ORC) for urothelial carcinoma do not factor the inherent stage selection bias or surgical experience. Methods We compared the perioperative outcomes of 229 RARC and 335 ORC at a single tertiary referral centre with propensity score matching and multiple regression models, when controlling for tumour and patient characteristics, surgeon's experience and type of urinary diversion. Results RARC had less major complications (19.8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Fifteen studies have described PSM, with a total of 3710 patients 13 15 , 17 , 25 , 26 , 28 , 31 35 , 38 40 . Heterogeneity test results suggest I 2 =0%, using the fixed-effects model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen studies have described PSM, with a total of 3710 patients 13 15 , 17 , 25 , 26 , 28 , 31 35 , 38 40 . Heterogeneity test results suggest I 2 =0%, using the fixed-effects model.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of 30-day 13 , 15 , 25 , 34 40 and 90-day 13 15 , 25 , 30 32 , 34 , 36 , 38 , 41 overall complication rate, we found that iRARC approaches had a decreased risk of the overall complication rate (30 days: OR: 0.53; 95% CI 0.33–0.87; P =0.012 Fig. 5 A; 90 days: OR: 0.87; 95% CI 0.77–0.98; P =0.019 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the NIS does provide details regarding robotic versus open surgery type, no reliable information is available if urinary diversion was performed extracorporeally or intracorporeally in RARC patients. 30,31 Moreover, the conceptualization and reporting guidelines of the NIS strongly prohibits reporting low numbers of events to preserve the nonidentifiable nature of its population. As a consequence, marginal differences may have not been captured within the current manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, median length of stay (LOS) was shorter in RARC (6 vs. 7days; p < 0.001). Conversely, median THC (31,486 vs. 27,162$; p < 0.001) were higher in RARC. Multivariable logistic regression-derived odds ratios addressing transfusion (0.49), intraoperative (0.53), wound (0.68), and pulmonary (0.71) complications favored RARC (all p < 0.01).…”
mentioning
confidence: 87%
“…Some studies even indicate cost savings in high-volume centers compared to open surgery [ 5 , 8 , 9 , 10 ]. Of great importance, lower morbidity, with at least equivalent oncologic outcomes compared with the open approach, has been proven for almost all robot-assisted interventions [ 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%